Brazilian doctors' perspective on the second opinion strategy before a C-section - Maria José Duarte Osis; José Guilherme Cecatti; Karla Simônia de Pádua; Anibal Faúndes
OBJECTIVE: To describe the opinion of doctors who participated in the Latin American Study on Cesarean section in Brazil regarding the second opinion strategy when faced with the decision of performing a C-section. METHODS: Seventy-two doctors from the hospitals where the study took place (where the second opinion was routinely sought) and 70 from the control group answered a pre-tested self-administered structured questionnaire. Descriptive tables were prepared based on the frequency of relevant variables on opinion of physicians regarding: effectiveness of the application of the second opinion strategy; on whether they would recommend implementation of this strategy and reasons for not recommending it in private institutions; feasibility of the strategy implementation and reasons for not considering this implementation feasible in private institutions. RESULTS: Half of the doctors from the intervention hospitals (50%) and about two thirds of those in the control group (65%) evaluated the second opinion as being or having the potential of being effective/very effective in their institutions. The great majority of those interviewed from both intervention and control hospitals considered this strategy feasible in public (87% and 95% respectively) but not in private hospitals (64% and 70% respectively), mainly because in the latter the doctors would not accept interference from a colleague in their decision-making process. CONCLUSION: Although the second opinion strategy was perceived as effective in reducing C-section rates, doctors did not regard it feasible outside the public health system in Brazil.